SPY ROBOT FOR MILITARY APPLICATION USING WI-FI MODULE - Aleena Johny; Sony, Nikhil T; Augustine, Dileep; A E, Hasna; V R, Deepa (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we will deliberate how to control a six wheeled robot using Wi-Fi module through an android mobile phone. A new version of wireless controlled robot is proposed for spying purpose which is mostly in military application as well as in disasters area. This robot which is a movable spy robot with wireless system. The spy robot consists of an IP camera, DC motors and servo motors for camera locations and guns. The sensors used for temperature and humidity detection and the movement of device is controlled by six movable wheels. This device powered by either regular lithium rechargeable ion batteries or solar cells.We are using smartphone camera as IP camera to capture livestreaming video surrounding the robot and that information will get appeared in user’s smartphone GUI window. The camera which is fixed on the robot will take the video livestreaming and this information get sent back to user’s smartphone using Wi-Fi wireless system. In this robot, we are using a gun which operates according to user’s instruction through smartphone.Keywords- Arduino, Wi-Fi module, Sensors, IP camera, Android application, Weapons.In this paper, we will deliberate how to control a six wheeled robot using Wi-Fi module through an android mobile phone. A new version of wireless controlled robot is proposed for spying purpose which is mostly in military application as well as in disasters area. This robot which is a movable spy robot with wireless system. The spy robot consists of an IP camera, DC motors and servo motors for camera locations and guns. The sensors used for temperature and humidity detection and the movement of device is controlled by six movable wheels. This device powered by either regular lithium rechargeable ion batteries or solar cells.We are using smartphone camera as IP camera to capture livestreaming video surrounding the robot and that information will get appeared in user’s smartphone GUI window. The camera which is fixed on the robot will take the video livestreaming and this information get sent back to user’s smartphone using Wi-Fi wireless system. In this robot, we are using a gun which operates according to user’s instruction through smartphone.